GHRAT: Global Heat Risk Assessment Toolbox - Xuewen Lei (18138637) (2025)
Existing assessments remain largely confined to academic research. Practical tools are available only for cities in developed countries. We develop GHRAT, the first globally consistent and ready-to-use toolbox that enables heat risk assessment for any location worldwide. Highlights: GHRAT is the first ready-to-use toolbox for heat risk assessment for any location worldwide, which accepts diverse input data and supports multiple heatwave definitions and enables early heat risk monitoring. GHRAT bridges scientific research and practical applications such as urban climate planning. A novel Multidimensional Social Vulnerability Index (MSVI) is proposed and incorporated.